Investigation of impact strength at different infill rates biodegradable PLA constituent through fused deposition modeling. (2022) - Dharmalingam, G.; Arun Prasad, M.; Salunkhe, Sachin
Abstract: Polylactic Acid (PLA) is a natural source of corn, cassava, and sugarcane which is an economically produced renewable, biodegradable, compostable, and bio plastic resource of this world. It plays an important role in automobile, aerospace, and consumer applications. Moreover, the PLA was in research and development with high expectations for the industrial consumer, moving towards the development of a sustainable vehicle and the goal is greatly contributed to environmental friendly applications such as in two-wheeler and four-wheeler vehicles. The present investigation consists of different infill rates (50%, 75% & 100%). PLA was performed for two-wheeler mudguard material for improving the property through additive manufacturing (AM) followed by fused deposition modeling (FDM). Based on the literature survey, it was found that FDM printed PLA's impact strength was lower than that fabricated through the Injection molding (IM) process due to improper selection of printing process parameters. In order to overcome this drawback were taken into account and to make a good environmentally friendly and biodegradable material was chosen as PLA. Finally, it was observed that the FDM-based PLA deposition has higher impact strength than IM because of introducing the printed sample of On-edge orientation and 100% infill rate. The finite element analysis (FEA) was performed to assess the impact strength of PLA at different infill rates by using the ANSYS software 17.2. The simulation results were compared with the experimental results, it was found that almost close to each other.